SISTEM MONITORING DETAK JANTUNG MENGGUNAKAN MIKROKONTROLER - Santoso, Gatot; -, Subandi; Hani, Slamet; Nugroho, Agung Wahyu (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2019)
The heart is a human organ that has a vital function. Small flaws in the heart organ can have a big effect on our body. In general, our heart beats around 60-100 times in one minute. If you exceed 100 times and less than 60 times every minute means your heart is experiencing an abnormal beat. Because some patients who suffer from heart need the automation of early detection. The development of electronic technology makes it possible for heart examinations to be carried out by the patient himself. This research aims to design and build a device to monitor heart rate using a microcontroller. Noise suppression on the ECG signal, heart rate data that has been detected and processed will be compared with normal and abnormal values ​​of the heartbeat. Furthermore, the microcontroller will determine how the heart condition is detected. From the results of the study the heart rate monitoring system using a microcontroller input voltage of 3.7 V DC was changed by the step up module to 5 V DC with a magnitude of error percentage of 0.863% and a charger module used to charge batteries with 4.2 V DC voltage and the magnitude of the error percentage amounted to 0.119%. The amped pulse sensor has an output voltage value of 2.4 V when it is relaxed and 2.6 V when it is beat, and this sensor has a constant and significant output voltage value in accordance with the rhythm of the heartbeat. The heart rate monitoring tool that is made can measure accurately and precisely, because it has a fairly small average error value of 1,727%.